Weed suppression and crop performance of rice (cv. BRRI dhan29) as influenced by application of different crop residues - Sheikh, Md Abdul Halim; Uddin, Md Romij; Salam, Md Abdus; Sarker, Uttam Kumer; Haque, Md Anamul (Fundamental and Applied Agriculture, 2017)
Recent agriculture is productivity-oriented and relies principally on artificial inputs to tackle weeds and other pest problems. Exhaustive herbicide apply to control weeds over the last few decades is posing severe ecological and environmental threats to the globe. The presence of crop residues on the soil surface as mulch suppresses weeds through allelopathy and thus reduces a greater reliance on herbicides. Considering mentioned issue an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from December 2014 to June 2015 to evaluate the effect of time of application of different crop residues on weed management and crop performance of rice. The experiment consists of three time of crop residues application; i) crop residues application before transplanting, ii) crop residues application one week after transplanting, and iii) crop residues application two weeks after transplanting and five different crop residues treatments such as no weeding and no crop residues, sorghum residue, maize residue, mustard residue, and rice residue in dried condition including shoot and leaves together. The experiment was laid out in a split plot design with three replications. Four weed species belonging to three families infested the experimental plots. Weed population and weed dry weight were significantly affected by time of crop residues application and crop residues treatment. The maximum weed growth was noticed with the application of crop residues two weeks after transplanting and the minimum was found with application of crop residues before transplanting treatment. Yield and yield contributing characters produced by application of crop residues before transplanting was the highest among the time of application. The highest reduction of grain yield was obtained in no weeding treatment while sorghum crop residue reduced the lowest grain yield. Similarly, most of the yields contributing characters were highest that are obtained from sorghum crop residues treatment. BRRI dhan29 under applied crop residues before transplanting treatment condition produced the highest grain and straw yields followed by applied crop residues one week after transplanting. Results of this study indicate that different crop residues showed potentiality to suppress weed growth. Therefore, crop residues might be used as an alternative tool for weed management.